Studies on production techniques of some herb plants: II Row spacing and cutting height of dill herb (anethum graveolens L.) - Hälvä, S. (Agricultural and Food Science, 1987)
A study was undertaken to determine the row spacing and cutting height of dill to produce a good quality herb in terms of high proportion of leaves. The row spacings were 12.5 or 25 cm, and the herb was harvested to the stubbles of 7.5, 11 or 15 cm. The greatest dry leaf yield, 8 kg/100 m2, was achieved with the narrow row spacing and lowest stubble. The proportion of leaves of the dry herb was highest (68 %) when cut to the highest stubble. The difference in the yields between the cuttings of 7.5 and 15 cm was significant, only. The relation between the dry and fresh yields (11 %) remained unaffected.